South China Karst 1 - Chuxing, Huang (ZRC, 1998)
The book is a results of the scientific co-operation between the Karst Research Institute at ZRC SAZU, the Yunnan Institute of Geography and Institute of Geology of the Chinese Academy of Sciences. The researches were carried out near Liupanshui, the western part of Guizhou, in karst between the mountains in Guizhou and Yunnan Plateau, in the area of Lunan stone forests and in cone-karst at Xichou, Yunnan. General characteristics of the areas, lithological and structural properties, geomorphological, speleological and hydrogeological characteristics are presented, as well as various types of land use and their environmental impacts.